SHRM Dimensions, Work Engagement and Intention to Quit: LinkedIn As a Data Source - Melhem, Yahya S.; Al-Fawareh, Hani F. (Jordan Journal of Business Administration, 2024)
The purpose of this study is to investigate the impact of strategic human-resource management (SHRM) on employees’ intention to quit, mediated by work engagement in the construction sector in GCC countries. The major findings of this study indicate that strategic human-resource management (SHRM) has a direct positive impact on work engagement and an indirect negative impact on employees’ intention to quit through work engagement. The study also indicated that work engagement has a direct negative impact on employees’ intention to quit. Structural equation modeling was employed to analyze data collected from 612 participants via a LinkedIn dataset. All participants work in the construction sector in Gulf States (GCC countries) and are members at LinkedIn as a professional social-networking site. Social-media network LinkedIn was employed to collect the data required for analysis. The study offers evidence and guidance for HRM practitioners for direct HRM practices and SHRM constructs in fostering work engagement and managing employees’ intention to quit. There is a lack of research examining the impact of SHRM and its components on employees’ intention to quit, mediated by work engagement. Thus, this study confirms the argument that SHRM can be an effective approach to influence employees’ intention to quit through work engagement.